2018
DOI: 10.14781/mcd.386035
|View full text |Cite
|
Sign up to set email alerts
|

Sosyal Bi̇lgi̇ler Ve Coğrafya Öğretmen Adaylarinin Zi̇hi̇n Hari̇talarinda Günümüz Dünya Sorunlari

Abstract: ÖzetBu araştırma öğretmen adaylarının zihin haritalarına yansıyan günümüz Dünya sorunlarını tespit etmek amacıyla yapılmıştır. Nitel yaklaşıma dayalı olarak gerçekleştirilen bu araştırmada nitel araştırma desenlerinden olgubilim deseni kullanılmıştır. Araştırmanın katılımcılarını Karadeniz Teknik Üniversitesi Coğrafya Öğretmenliği lisans programında öğrenim gören 100 öğretmen adayı ile Sosyal Bilgiler Öğretmenliği lisans programında öğrenim gören 200 öğretmen adayı oluşturmaktadır. Araştırmada veri toplama ara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…Again, in the field of social studies, there are studies in the literature by using mind maps to have the target audience make some designs and get their opinions on some issues (Aksoy & Koç, 2012;Öner, 2022;Şeyihoğlu, Sever & Özmen, 2018;Tunçel, 2002). In addition to these, perceptions towards social studies course or social studies have also been determined through metaphors or open-ended questions in the literature (Alazzi & Chiodo, 2004;Berksan, 2018;Bolat, 2020;Gömleksiz et.…”
Section: Ortaokul öğRencilerinin Sosyal Bilgiler Dersine Yönelik Algı...mentioning
confidence: 99%
“…Again, in the field of social studies, there are studies in the literature by using mind maps to have the target audience make some designs and get their opinions on some issues (Aksoy & Koç, 2012;Öner, 2022;Şeyihoğlu, Sever & Özmen, 2018;Tunçel, 2002). In addition to these, perceptions towards social studies course or social studies have also been determined through metaphors or open-ended questions in the literature (Alazzi & Chiodo, 2004;Berksan, 2018;Bolat, 2020;Gömleksiz et.…”
Section: Ortaokul öğRencilerinin Sosyal Bilgiler Dersine Yönelik Algı...mentioning
confidence: 99%
“…The aim of geography teaching should not be to overload information by using dense texts; visuals should be used to transfer more understandable, concrete, and permanent information (Akınoğlu, 2005). In many studies, it has been found that in geography teaching processes where visuals are used, students are more enthusiastic and actively participate in the process, and their academic achievement increases (Sekin & Ünlü, 2002;Coşkun, 2003;Eker, 2003;Tomal, 2004;Ulusoy & Gülüm, 2009;Sever, Budak, & Yalçınkaya, 2009;Demirkaya & Ayas, 2015;Demirkaya & Karacan, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It has been noticed that studies conducted in the field of education in Turkey use the concepts of "global problems" or "today's world problems", although they have the same content. As a matter of fact, the title of global problems has been preferred in some studies (Durmuş, 2020;Kan, 2009a;Kan, 2020;Kitapçı, 2017;Palaz 2017;Palaz and Akbaba, 2018;Yiğit, 2019), and the title of today's world problems in some studies (Akdağ and Yıldız, 2020;Avcı and Gümüş, 2017;Kılıçoğlu, Karakuş and Öztürk, 2012;Mercan and Sarı, 2019;Özmen, 2015;Şeyihoğlu, Sever and Özmen, 2018;Turan, 2009;Yazıcı, 2013). In the literature on global problems and today's world problems, the intensity of studies focusing on attitude and perception and conducted with pre-service teachers is remarkable.…”
Section: Global Problems Through the Eyes Of 8 Th Grade Students Introductionmentioning
confidence: 99%